Marriage and Procreatio in Ancient Rome - Novkirishka-Stoyanova, Malina (Yearbook of the Law Department, 2020)
The study presents the Roman concept of marriage as a union of spouses with the purpose of giving birth, raising and educating the children. In parallel are presented the social roles of mother and father in the Roman family and the legal framework of their status. The article shows some of the main points of promoting the birth rate increase and stabilizing the procreative function of marriage for demographic and political purposes. Some of them – and especially the protection of the interests of children, which can be a starting point for the modern development of the system for stabilizing the marriage and the family to face the social challenges of the XXI century.